(untitled) (International Journal of Food and Nutritional Sciences, 2024)
The intranet message system is a communication platform that enables users with in anorganization to send and receive messages, share files, and collaborate with each other securely over a Local Area Network(LAN) with a radius of 200meters.TheIntranetMessageSystemisaveryeffective internal communication solution that allows employees to interact and collaborate more easily It consists of two primary components are ’Server Module’ and the ’Clients Module’. The Server Module is in charge of securely managing all communication, ensuring that everything functions smoothlyandreliablywhilemaintainingastablenetwork.TheClientsModule,ontheotherhand, allows employees to log in using only their nickname, server name, and port number, providing themwithinstantaccesstochatrooms.Onceloggedin,userscanchoosebetween’PublicChatting’, whereeveryoneinthechatroomcanseetheconversation,and’PrivateChatting,’whichallowsfor more personal, one-on-one chats. This adaptability makes the system suitable for both group collaboration and private chats. the system incorporates emotive icons, which allow users to graphically convey their emotions while chatting.This feature improves communication by making it more personalized and engaging. Overall, the system aims to provide employees with an efficient, secure, and entertaining communication experience